QUALITY OF CHILLED CANINE SEMEN IN TRIS-EGG YOLK EXTENDER SUPPLEMENTED WITH SERICIN - Khye, Kim Chwin; Yusuf, Tuty Laswardi; Satrio, Faisal Amri; Karja, Ni Wayan Kurniani (Jurnal Kedokteran Hewan, 2021)
ABSTRACTThe objective of this research was to evaluate the quality of chilled canine semen in Tris-egg yolk (TEY) extenders containing different concentrations of sericin. Semen were collected from four dogs by massage method. Canine semen was collected using sterile urine pots and evaluated. Sperm-rich fractions were pooled and divided into four equal aliquots, which were then diluted with TEY extenders supplemented with different concentrations of sericin (0%, 0.1%, 0.25%, 0.5%). The diluted semen aliquots were preserved at 4 in sterile centrifuge tubes and were then evaluated for spermatozoa motility, viability, plasma membrane integrity and acrosome integrity every 12 hours up to 72 h. The TEY extenders supplemented with 0.25% and 0.5% sericin resulted in higher spermatozoa motility and viability at 72 h compared to other TEY extenders (P0.05). The integrity of plasma membrane and acrosome of spermatozoa showed no significant differences among the groups extenders at 72 h. In conclusion, sericin in concentration of 0.25% and 0.5% were able to prevent the motility and viability of canine spermatozoa after storage for 72 h.